On marine wind power expressiveness: Not just an issue of visual impact - Paolinelli, Gabriele; Fortuna, Lorenza; Marinaro, Ludovica; Valentini, Antonella (Frontiers in Energy Research, 2022)
Technological research for the exploitation of marine energy has produced such significant advances to be promising in the process of transition to renewable resources. However, many issues hinder the exploration of these scenarios, not least the cultural ones concerning the visual impacts of these technologies. Assuming that ‘protecting’ means preserving without banning evolutive changes, seascape protection and ecological transition are not alternatives because both converge towards sustainability. Nevertheless, scientific concepts, technical practices, social perceptions and the related decisions and actions show contradictions and conflicts. Inside the complex challenge of ecological transition, clean energy availability arises as a necessary and demanding condition. This article proposes a landscape design critical perspective about the opportunity of understanding and expressing contemporaneity also through its changes in habitats and life. A focus on marine wind turbine’s visual impacts is proposed as a sample of a general discourse on technical and social perceptions in a context of both cultural and spatial transition. Site-specific critical visions have to be imagined and discussed to produce not business as usual transformations. This paper aims to show that positions mostly based on visual impact are not enough to express the cultural dimension of the ecological transition.